2009
DOI: 10.7210/jrsj.27.87
|View full text |Cite
|
Sign up to set email alerts
|

How Quickly Should Communication Robots Respond?

Abstract: This paper reports a study about system response time (SRT) in communication robots that utilize human-like social features, such as anthropomorphic appearance and conversation in natural language. Our research purpose established a design guideline for SRT in communication robots. The first experiment observed user preferences toward different SRTs in interaction with a robot. In other existing user interfaces, faster response is usually preferred. In contrast, our experimental result indicated that user pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Moreover, although some applications using CF in speech generation exist, e.g. [20] showed that a turn-initial CF produced by a robot significantly improved the user's impression of longer response times, the design of cognitive artificial agents, equipped with limited functionality in recognizing and producing the form-function relationship associated with CFs, still represents a challenging goal. In this paper we attempt to pursue these overall goals by reporting on the form-function relationship of Slovak conversational fillers uh and mm in task-oriented dyadic spontaneous human-human conversations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although some applications using CF in speech generation exist, e.g. [20] showed that a turn-initial CF produced by a robot significantly improved the user's impression of longer response times, the design of cognitive artificial agents, equipped with limited functionality in recognizing and producing the form-function relationship associated with CFs, still represents a challenging goal. In this paper we attempt to pursue these overall goals by reporting on the form-function relationship of Slovak conversational fillers uh and mm in task-oriented dyadic spontaneous human-human conversations.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study [20] revealed that individual people have preferable ranges of speed while walking together with a robot. Studies of conversational interactions [12,17,18] have found that the use of speech by robots during degraded states can effectively reduce customer frustration. By combining those ideas, our solution is to choose an acceptable slow speed, and to use speech to increase people's tolerance toward that slow speed.…”
Section: Baggage Carryingmentioning
confidence: 99%
“…For example, if the operator's attention is focused too much on a single robot, then the other robots may be overlooked and operating in degraded states for a long time, which may eventually lead robots to dangerous states or decrease the total performance of the robot team. For robots conducting social interactions with people, degraded responses by the robots can cause frustration and a negative impression toward the robots [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, since users might feel uncomfortable during slow responses or long pauses, robot response time is critical. To solve such problems, we implemented a conversational filler to buy time [29]. When the operator needs a few seconds, he/she executes a conversational filler behavior to notify listeners that the robot is going to respond soon.…”
Section: Conversational Fillersmentioning
confidence: 99%